A STUDY ON IMPACT OF ASSET LIABILITY MANAGEMENT ON THE LIQUIDITY AND PROFITABILITY OF SELECTED COMMERCIAL BANKS IN INDIA - Behera, Sumanta; Satapathy , Sanjaya Kumar (International Journal of Psychosocial Rehabilitation, 2020)
The technique of Asset-Liability-Management (ALM) is an inclusive and active basis for measuring,checking and handling the market risk of a bank. It is the management of balance sheet structure (Asset Liability) in such a way that the net incomes from interest are maximized within the overall risk-preference of the banks.Asset-Liability-Management (ALM) indicates the capacity of earning profits by the banks and the financial soundness of the banks. A lot of studies have been conducted in area of Asset-Liability-Management (ALM) and its impact on profitability position of Indian and as well as the foreign banks. But, there are no remarkable researches have been conducted in the area of Asset-Liability-Management (ALM) and its impact on the liquidity and profitability of Indian commercial banks. So, this is an attempt to study the impact of Asset-Liability-Management (ALM) on the liquidity and profitability of selected commercial bank in India. The study is based on secondary data. The secondary data have been collected through well designed strategy and these have been collected from various e-journals, e-magazines, e-annual reports of commercial banks and RBI website and from various reputed websites. The collected data have been classified and tabulated according to the requirements of the study. There are various tools like percentage calculations; valid percentage calculation, comparative statement analysis and ratios analysis have been used for analysis and interpretations of results. It is found that ALM is a successful tool for risk management. It provides the necessary framework to define measures, monitor, modify and manage these risks.